Fundraising and Strategic Planning : Innovative Approaches for Museums - Decker, Juilee (Innovative approaches for museums., 2015)
"Fundraising and Strategic Planning : Innovative Approaches for Museums appraise strategies museums employ to raise funds including admission prices, membership categories, donor and affinity groups, and specialized event-driven efforts while examining new crowdfunding models such as Kickstarter and Indiegogo"--Provided by publisher